Respuesta :

Answer:

8

Step-by-step explanation:

So we have 12 1/2 - (-4 1/2)

6-(-2)

6+2

8

Question :-

[tex] \sf12 \frac{1}{2} - ( - 4 \frac{1}{2} ) = \boxed{ ? }[/tex]

____________________

Solution :-

Given Information :-

  • Fraction 1 ➢ [tex] \sf12 \frac{1}{2} [/tex]
  • Fraction 2 ➢ [tex] \sf -4 \frac{1}{2} [/tex]
  • Operation Subtraction

To Find :-

  • The difference between two fractions

Calculation :-

[tex] \sf: \implies \sf12 \frac{1}{2} - ( - 4 \frac{1}{2} ) = \boxed{ ? }[/tex]

Firstly, converting mixed fractions to improper fractions, We get,

[tex] \sf: \implies \frac{25}{2} - ( - \frac{9}{2} ) = \boxed?[/tex]

Now, solving the parentheses, We get,

[tex] \sf: \implies \frac{25}{2} + \frac{9}{2} = \boxed ?[/tex]

Since, We have like terms, We will directly add up the two fractions, We get,

[tex] \sf: \implies \frac{25 + 9}{2} = \boxed?[/tex]

Calculating further, We get,

[tex] \sf: \implies \frac{34}{2} = \boxed?[/tex]

Bringing the fraction to it's lowest terms, We get,

[tex] \sf: \implies \frac{ \cancel{34} \: \: \tiny{7}}{ \cancel2} = \boxed7[/tex]

[tex] \sf :\implies \sf12 \frac{1}{2} - ( - 4 \frac{1}{2} ) = \red{ \boxed{ \bf7 }}[/tex]

____________________

Final Answer :-

  • [tex] \sf \sf12 \frac{1}{2} - ( - 4 \frac{1}{2} ) = \red{ \boxed{\bf7 }}[/tex]

____________________

ACCESS MORE